2022
DOI: 10.1002/joc.7602
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and projection of precipitation in Pakistan using the Coupled Model Intercomparison Project Phase 6 model simulations

Abstract: This study aimed to evaluate the performance of global climate models (GCMs) from the family of the Coupled Model Intercomparison Project Phase 6 (CMIP6) in the historical simulation of precipitation and select the best performing GCMs for future projection of precipitation in Pakistan under multiple shared socioeconomic pathways (SSPs). The spatiotemporal performance of GCMs was evaluated against the Climate Research Unit (CRU) data in simulating annual precipitation during 1951–2014, using the Taylor diagram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 107 publications
2
14
0
Order By: Relevance
“…Meanwhile, IFAHP, CRITIC, and ICWGT used in this study for assessing flood risk could make results obtained quickly, which was helpful for the division of flood risk areas. In previous studies, Abbas et al (2022) found that under the high-forcing scenario (SSP5-8.5), the trend of extreme precipitation events in CPEC increased significantly, and the tendency of extreme precipitation events in summer also increased significantly, which is consistent with the conclusions of this article. In the verification of temperature simulation in Thailand (Suchada et al, 2021), the simulation results and accuracy of CNRM-CM6-1 were affirmed, so the accuracy of the simulation results based on CNRM-CM6-1 could be considered to be guaranteed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Meanwhile, IFAHP, CRITIC, and ICWGT used in this study for assessing flood risk could make results obtained quickly, which was helpful for the division of flood risk areas. In previous studies, Abbas et al (2022) found that under the high-forcing scenario (SSP5-8.5), the trend of extreme precipitation events in CPEC increased significantly, and the tendency of extreme precipitation events in summer also increased significantly, which is consistent with the conclusions of this article. In the verification of temperature simulation in Thailand (Suchada et al, 2021), the simulation results and accuracy of CNRM-CM6-1 were affirmed, so the accuracy of the simulation results based on CNRM-CM6-1 could be considered to be guaranteed.…”
Section: Discussionsupporting
confidence: 92%
“…These models were commonly used by others. Abbas et al (2022) used these four models for climate simulation in Pakistan. The CESM2 simulations exhibit agreement with satellite-era observations of the climate mean state, seasonal cycle, and interannual variability that are among the closest coupled climate model in the present CMIP6 archive (Danabasoglu et al, 2020).…”
Section: Precipitation Data Setsmentioning
confidence: 99%
“…This increase in the northern region made it more vulnerable to climate change. Previous studies conducted in the region have shown similar temperature and precipitation indices increase in northern parts (Abbas et al, , 2014S. Ullah et al, 2022).…”
Section: Discussionsupporting
confidence: 63%
“…The annual precipitation will increase in the range of 3.5-12.8% in the mid-and late centuries in the region. The two studies that employed a fine-resolution General Circulation Model (GCM) (∼25 km) and the latest CMIP6 have projected wetter summers in the UIB in the future (Ali et al 2021;Abbas et al 2022). Glaciers in the region will not be able to retain their mass despite the increase in precipitation because the increase in temperatures will make the current mass balance negative (Lutz et al 2016).…”
Section: Introductionmentioning
confidence: 99%